Chapter Monitoring of the evolution of "barene" borders and the safeguard of the Venice Lagoon morphology: a contribution from the Coastal Change From Space Project results - D'Ascola, Filippo (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
This research proposes the acquisition of a time series from optical satellites to observe changes in the Venice lagoon, an ecosystem which is very challenging to monitor by means of in situ survey activities, let alone using remote sensing techniques, given the presence of land and sandbars (vegetated intertidal areas). The work describes the specific validation process performed by ISPRA on the results obtained as applied on some target sites of the Venice Lagoon, both natural and partially artificial islands, using fully artificial islands as reference.